Pro-hepcidin: expression and cell specific localisation in the liver and its regulation in hereditary haemochromatosis, chronic renal insufficiency, and renal anaemia. Issue 5 (13th April 2004) - Kulaksiz, H; Gehrke, S G; Janetzko, A; Rost, D; Bruckner, T; Kallinowski, B; Stremmel, W
Abstract : Background and aims: The hepatic peptide hormone hepcidin, which has recently been isolated from human plasma and urine, is thought to be a central regulator of iron homeostasis. We investigated the presence and cellular localisation of hepcidin in the liver and developed a non-invasive assay to analyse its regulation in patients with hereditary haemochromatosis (HH), chronic renal insufficiency (CRI), and renal anaemia (RA). Methods: Expression and localisation of hepcidin was shown by reverse transcription-polymerase chain reaction, western blot, immunocytochemistry, and immunofluorescence in human and guinea pig liver. Serum concentrations were determined in various groups of patients using a sensitive enzyme linked immunosorbent assay (ELISA). Results: Western blot analysis with region specific antibodies identified a 10 kDa peptide corresponding to the apparent molecular mass of pro-hepcidin. Localisation studies revealed that pro-hepcidin is expressed at the basolateral membrane domain of hepatocytes and is also present in blood. We developed a stable sensitive ELISA for detection and determination of pro-hepcidin in human serum. Mean pro-hepcidin level in human serum of healthy volunteers was 106.2 ng/ml. Enhanced levels of pro-hepcidin (148.1 ng/ml) were found in patients with CRI but normal haemoglobin values, indicating that the kidneys may metabolise and/or eliminate the circulating hormone. In contrast, concentrations of pro-hepcidin were significantly decreased in patients with HH (70.2 ng/ml) and also in patients with RA (115.0 ng/ml) compared with the CRI group. Conclusions: From the detection of pro-hepcidin in human serum, we conclude that the prohormone may be involved in the regulation of iron metabolism in HH. Decreased pro-hepcidin levels could play an important role in the pathogenesis of HH.